FRAMING BERITA CAPRES-CAWAPRES PADA PILPRES 2019 DI HARIAN UMUM REPUBLIKA DAN KORAN TEMPO (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2019)
This research tries to find out whether there are media aligments towards the two pairs of Presidential Candidates and Candidates for Vice-President 2019-2024, Joko Widodo –Ma’ruf Amin and Prabowo Subianto –Sandiaga Uno. The researcher has chosen Harian Umum Republika and Koran Tempo as the research subjects. Aside from being a media conglomerate, CEO of PT Mahaka Media Tbk, which is the legal entity of Republika, Erick Thohir, is also the Chairperson of the TKN Jokowi-Ma'ruf Amin, which is assumed to have access to influence editorial policies. While Koran Tempo was chosen because it was considered professional and independent according to the media record. This research uses framing analysis of Zhongdang Pan and Gerald M. Kosicki models. The results of the research showed that the Harian Umum Republika  tended to be more independent in carrying out journalistic duties, but Koran Tempo favored to the candidates Jokowi-Ma'ruf Amin. Keywords: media alignments, media framing, 2019 cawapres presidential candidates